2016
DOI: 10.1074/jbc.m115.686246
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Domain Mediates Tetramerization of α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid (AMPA) Receptors

Abstract: AMPA receptors (AMPARs) mediate fast excitatory neurotransmission in the central nervous system. Functional AMPARs are tetrameric complexes with a highly modular structure, consisting of four evolutionarily distinct structural domains: an amino-terminal domain (ATD), a ligand-binding domain (LBD), a channel-forming transmembrane domain (TMD), and a carboxyl-terminal domain (CTD). Here we show that the isolated TMD of the GluA1 AMPAR is fully capable of tetramerization. Additionally, removal of the extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 55 publications
5
44
0
Order By: Relevance
“…Thus, minor overall movements in the GluK4-GluK4 dimer model compared with the GluK1-GluK1 dimer seem to be necessary in order to avoid steric clash. This would be consistent with the previous suggestion that the N-terminal domain of GluK5 plays an important role in receptor assembly (Kumar and Mayer, 2010) and that the transmembrane domain mediates tetramerization of AMPA receptors with other domains playing modulatory roles (Gan et al, 2016). However, direct evidence must await a full-length heteromeric structure consisting of low-affinity and high-affinity kainate receptor subunits.…”
Section: Gluk4 Dimer Interfacesupporting
confidence: 90%
“…Thus, minor overall movements in the GluK4-GluK4 dimer model compared with the GluK1-GluK1 dimer seem to be necessary in order to avoid steric clash. This would be consistent with the previous suggestion that the N-terminal domain of GluK5 plays an important role in receptor assembly (Kumar and Mayer, 2010) and that the transmembrane domain mediates tetramerization of AMPA receptors with other domains playing modulatory roles (Gan et al, 2016). However, direct evidence must await a full-length heteromeric structure consisting of low-affinity and high-affinity kainate receptor subunits.…”
Section: Gluk4 Dimer Interfacesupporting
confidence: 90%
“…; Gan et al . ). We then asked if the mutants (N63S and N363S) form functional tetramers, and BN‐PAGE analysis demonstrated that glycosylation mutants (N63S and N363S) were unable to form tetramers and accumulated at higher sizes (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…It is well accepted that glutamate receptors form tetrameric subunits complexes (Mano and Teichberg 1998). WT GluA1 AMPA-Rs were detected on BN-PAGE predominantly as tetramers and, weakly, as monomers and dimers in neurons and HEK 293 cells (Greger et al 2002(Greger et al , 2003(Greger et al , 2006Vandenberghe et al 2005;Gan et al 2016). We then asked if the mutants (N63S and N363S) form functional tetramers, and BN-PAGE analysis demonstrated that glycosylation mutants (N63S and N363S) were unable to form tetramers and accumulated at higher sizes (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…These changes are in stark contrast to the S2-M4 linkers in subunits B and D, which maintain their relative positioning. The unprecedented conformational changes in the subunits A/C S2-M4 linkers that occur during channel opening support the importance of the M4 segments for iGluR function 3739 and suggest a possible contribution of these linkers to the open pore extracellular vestibule.…”
Section: Gating Mechanismmentioning
confidence: 81%